Integrating stakeholder and network theory : The specific case of wild national park rural tourism - Nogueira, Sónia (2021)
This study addresses the structure, nature and composition of stakeholder networks related to rural tourism in a Portuguese Wild National Park (WNP-Gerês), in particular, it examines their interactions along the following dimensions, marketing information, administrative resources, human resources, training and financial resources. This study examines the type and nature of interactions among different stakeholders within a specific rural tourism destination. Among these, the marketing information network shows both high number of connections and high centrality indices, which may indicate that there is a significant share of information about common projects, products and services among stakeholders. In contrast, the training network evidenced the opposite pattern behavior. Since public policy measures can play an increasingly important role in shaping stakeholder networks within a tourism setting, the study also examines the influence of local public measures on the nature of stakeholder interactions. The methodological approach adopted in this study integrates both qualitative and quantitative techniques. The study contributes to a better understanding of how different local stakeholders are positioned in a complex structure of interactions, which are critical in providing useful directions to maximize potential opportunities that may contribute to promote rural tourism and local development efficiently.